2009
DOI: 10.2967/jnumed.108.058701
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of 123I-MIBG Scintigraphy in the Evaluation of Patients with Known or Suspected Primary or Metastatic Pheochromocytoma or Paraganglioma: Results from a Prospective Multicenter Trial

Abstract: Although 123I-MIBG has been in clinical use for the imaging of pheochromocytoma for many years, a large multicenter evaluation of this agent has never been performed. The present study was designed to provide a prospective confirmation of the performance of 123I-MIBG scintigraphy for the evaluation of patients with known or suspected primary or metastatic pheochromocytoma or paraganglioma. Methods A total of 81 patients with a prior history of primary or metastatic pheochromocytoma or paraganglioma and 69 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(77 citation statements)
references
References 21 publications
(20 reference statements)
0
73
1
3
Order By: Relevance
“…Even though 123/131 I-metaiodobenzylguanidine ( 123/131 I-MIBG) scintigraphy is an excellent functional imaging tool in adrenal PCC, it has demonstrated low sensitivity in extraadrenal PGL and metastatic PCC/PGL [11][12][13]. In recent years, 18 F-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography (PET) has been suggested as a preferred functional imaging tool in malignant PCC/PGL, particularly in SDH and von Hippel-Lindau (VHL) germline mutation tumours or when de-differentiated tumour is suspected [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Even though 123/131 I-metaiodobenzylguanidine ( 123/131 I-MIBG) scintigraphy is an excellent functional imaging tool in adrenal PCC, it has demonstrated low sensitivity in extraadrenal PGL and metastatic PCC/PGL [11][12][13]. In recent years, 18 F-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography (PET) has been suggested as a preferred functional imaging tool in malignant PCC/PGL, particularly in SDH and von Hippel-Lindau (VHL) germline mutation tumours or when de-differentiated tumour is suspected [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The reported sensitivity and specificity of MIBG scanning in patients with (suspected) pheochromocytoma range from 80 to 100% (17)(18)(19)(20)(21)(22). MIBG uptake correlates with the production of catecholamines (18).…”
Section: Discussionmentioning
confidence: 99%
“…False-negative scans are more frequent in those with the SDHB mutation or von HippelLindau syndrome-associated PHEO (41), probably due to lower expression of NET. In a prospective study in 140 patients, 123 I-MIBG showed specificity of 82% and sensitivity of 88% for PHEO and 67% for PGL (42). Patients with multiple endocrine neoplasia syndrome may also be evaluated with 123 I-MIBG to detect concurrent lesions in adrenal and thyroid glands.…”
Section: I/ 131 I-mibg For Imaging Of Neuroblastomamentioning
confidence: 99%